The SP‐TLR axis, which locally primes the nasal mucosa, is impeded in patients with allergic rhinitis - Larsson, Olivia (Clin Transl Allergy, 2021)
BACKGROUND: Substance P (SP) and toll‐like receptors (TLRs) contribute to airway disease, particularly during viral infection. We recently demonstrated that SP can act as an initial response to viral stimuli in the upper airway by upregulating TLRs in the nasal epithelia (the SP‐TLR axis). Patients with allergic rhinitis (AR) suffer from prolonged airway infections. The aim of the present study was to examine if patients with AR exhibit a disturbance in the SP‐TLR axis. METHOD: Human nasal biopsies and human nasal epithelial cells (HNEC) from healthy volunteers and patients with AR were cultured in the presence of SP. Epithelial expression of TLR4, neutral endopeptidase (NEP) and neurokinin 1 (NK1) were evaluated with flow cytometry and/or quantitative polymerase chain reaction after 30 min to 24 h. The effect of SP on nasal lipopolysaccharide‐induced interleukin‐8 (IL‐8) release was investigated. RESULTS: SP stimulation of tissue from healthy volunteers resulted in a transient increase of the TLR4 expression, whereas stimulation of AR patient‐derived material led to a delayed and prolonged upregulation of TLR4. NEP expression in HNEC was lower in AR than healthy controls whereas NK1 receptor expression was increased. SP pretreatment increased TLR4‐dependent IL‐8 expression in healthy controls, but not in AR. CONCLUSIONS: SP‐induced regulation of TLR4 in the human nasal mucosa is disturbed in AR. An altered SP‐mediated innate immune response may contribute to the dysfunctional and often prolonged responses to infection in AR.